2021
DOI: 10.1007/s10334-021-00980-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of glioblastoma tissue response mapping with physiologic BOLD imaging using precise oxygen and carbon dioxide challenge

Abstract: Objectives: Innovative physiologic MRI development focuses on depiction of heterogenous vascular and metabolic features in glioblastoma. For this feasibility study, we employed blood oxygenation leveldependent (BOLD) MRI with standardized and precise carbon dioxide (CO2) and oxygen (O2) modulation to investigate specific tumor tissue response patterns in patients with newly diagnosed glioblastoma. Materials and methods: Seven newly diagnosed untreated patients with suspected glioblastoma were prospectively inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Interestingly, oxygen modulation has been also recently proposed as a means to study cerebral perfusion through rapid transient hemoglobin desaturation with the potential to substitute contrast-based perfusion [ 202 , 203 , 204 ] with advantages also relating to the avoidance of gadolinium contrast use [ 205 ], but application in the study of brain tumors is still lacking. Independently of these developments, the possibility of precise end-tidal oxygen modulation in isocapnic conditions has been preliminarily investigated as a means to provide a novel “imaging biomarker” to detail glioblastoma lesion microvascular features during BOLD imaging, exploiting hypoxia and hyperoxia as BOLD contrasts [ 206 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Interestingly, oxygen modulation has been also recently proposed as a means to study cerebral perfusion through rapid transient hemoglobin desaturation with the potential to substitute contrast-based perfusion [ 202 , 203 , 204 ] with advantages also relating to the avoidance of gadolinium contrast use [ 205 ], but application in the study of brain tumors is still lacking. Independently of these developments, the possibility of precise end-tidal oxygen modulation in isocapnic conditions has been preliminarily investigated as a means to provide a novel “imaging biomarker” to detail glioblastoma lesion microvascular features during BOLD imaging, exploiting hypoxia and hyperoxia as BOLD contrasts [ 206 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Moving away from resting perfusion assessment, other approaches may be employed to investigate intrinsic tissue features by dissecting specific BOLD signal changes characteristics during gas control. A preliminary study demonstrated the feasibility of such technique, with a small cohort of glioblastoma patients exhibiting unique tissue response patterns during hypoxic, hyperoxic and hypercapnic stimuli ( Stumpo et al, 2021 ). For this reason, a longitudinal cohort study after optimization of the hypoxic stimulus is currently ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…During the echo-planar imaging (EPI) sequence acquisition, 160 volumes were acquired corresponding to a duration of circa 5 minutes. Acquisition parameters of T1-CE, FLAIR, T2 as per standard brain tumor protocol have been described in previously published article ( Stumpo et al, 2021 ). For a subgroup of patients, clinical-diagnostic work-up required execution of a gadolinium (Dotarem) enhanced DSC-MRI GRE-EPI, FOV 100 × 100 mm 2 , resolution 128 × 128, TR/TE 2040/36, FA 90°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical implications associated with the anatomical location of glioblastoma were analyzed in different articles, with a total of 107 articles in which a relationship was not made between the region of glioblastoma and a clinical implication [10,11,13,[18][19][20][21][22][70][71][72][73][74][75][77][78][79][80][81][82][83][84][85][87][88][89][90][91][92][93][94][95][96][97][98][99][100]104,105,[107][108][109][110][111][112][113][114][115][116]…”
Section: Discussionmentioning
confidence: 99%